Learning from the Experience of the COVID-19 Pandemic: A New Paradigm for Occupational Biohazard Assessment and Management - Durando, Paolo; Rahmani, Alborz; Montecucco, Alfredo; Dini, Guglielmo (La Medicina del Lavoro, 2023)
The COVID-19 pandemic has affected workplaces in many different aspects. In this scenario, Occupational Physicians played a crucial role in assessing and managing the risk of SARS-CoV-2 infection and associated diseases to guarantee workers’ health and the safety of workplaces. However, the pandemic experience has drawn attention to several critical issues in overall biohazard prevention and management strategies, originating from important knowledge gaps in our scientific understanding. An extensive analysis of the relevant hurdles that have emerged in our medical field can bring valuable lessons for the post pandemic future, not only in preparation for possible new pathogens with pandemic potential but also with principles and concepts applicable to managing all biological agents. In particular, a paradigm shift is needed to properly approach occupational diseases caused by infective agents, accurately define the “case”, assess exposure and possible causal relationship with work appropriately, and effectively manage the specific risk through implementing appropriate preventive and protective measures. In this framework, the Occupational Physician should expand his contribution based on his unique expertise and specific competencies, confirming his role as the go-to consultant in all occupational health matters, but also in a multidisciplinary approach, considering different scientific expertise and evidence.